(untitled) (Indian Journal of Public Health Research & Development, 2021)
Background : Poornima University, in collaboration with Jodhpur School of Public Health, hosted an insightful and interactive live global webinar on the topic of “From AIDS to COVID: The Rocky road of Public Health” on August 8, 2020. Findings: This report provides information about the coronavirus, the good and bad impact of COVID-19, and some of the major challenges that were faced all across the globe. Many questions are it the origin of the virus or the route of transmission of the virus remains unclear. But the good thing is that there were many innovations in the field of testing, repurposing of drugs, and rapid development of vaccines to reduce the spread of the pandemic. Conclusion: The findings show that a lot of questions are yet to be answered and that there is a need of focusing on public health. There were many learnings from this pandemic and one of the most important lessons was that the involvement of communities is a key step to face such global challenges. The pandemic is not going anywhere soon, and therefore, it becomes necessary to bring in change and sustain it for the future. The challenges faced during this pandemic have served as valuable lessons and it is vital to focus on the shortcomings to avoid such negative impacts around the world.